The Association between Some Demographic Characteristics and the Types of Miscarriage among Women in Rania City - Sharmin Abdalrahman Kareem; Sanna Hassan Abdulsahib (Kufa Journal for Nursing Sciences)
Background: Miscarriage or spontaneous abortion is one of the prevalent adverse reproductive outcomes, which seriously threatens maternal health around the world. Some demographic features might associate with an elevate risk of spontaneous miscarriage which include cervical incompetence, infection, previous history of miscarriage, maternal passive smoking, age, and body weight.